Consumption of nattokinase is associated with reduced blood pressure and von Willebrand factor, a cardiovascular risk marker: results from a randomized, double-blind, placebo-controlled, multicenter North American clinical trial - Jensen, Gitte S (Integr Blood Press Control, 2016)
OBJECTIVE: The objective of this study is to evaluate the effects of consumption of nattokinase on hypertension in a North American hypertensive population with associated genetic, dietary, and lifestyle factors. This is in extension of, and contrast to, previous studies on Asian populations. MATERIALS AND METHODS: A randomized, double-blind, placebo-controlled, parallel-arm clinical study was performed to evaluate nattokinase (NSK-SD), a fermented soy extract nattō from which vitamin K2 has been removed. Based on the results from previous studies on Asian populations, 79 subjects were enrolled upon screening for elevated blood pressure (BP; systolic BP ≥130 or diastolic BP ≥90 mmHg) who consumed placebo or 100 mg nattokinase/d for the 8-week study duration. Blood collections were performed at baseline and 8 weeks for testing plasma renin activity, von Willebrand factor (vWF), and platelet factor-4. Seventy-four people completed the study with good compliance. RESULTS: Consumption of nattokinase was associated with a reduction in both systolic and diastolic BP. The reduction in systolic BP was seen for both sexes but was more robust in males consuming nattokinase. The average reduction in diastolic BP in the nattokinase group from 87 mmHg to 84 mmHg was statistically significant when compared to that in the group consuming placebo, where the average diastolic BP remained constant at 87 mmHg (P<0.05), and reached a high level of significance for males consuming nattokinase, where the average diastolic BP dropped from 86 mmHg to 81 mmHg (P<0.006). A decrease in vWF was seen in the female population consuming nattokinase (P<0.1). In the subpopulation with low plasma renin activity levels at baseline (<0.29 ng/mL/h), an increase was seen for 66% of the people after 8-week consumption of nattokinase (P<0.1), in contrast to only 8% in the placebo group. CONCLUSION: The data suggest that nattokinase consumption in a North American population is associated with beneficial changes to BP in a hypertensive population, indicating sex-specific mechanisms of action of nattokinase’s effect on vWF and hypertension.